Pengaruh Komparasi, Justifikasi dan Sistem Tata Kerja Pelatihan Terhadap Realisasi Sertifikasi Pekerja PKWT Sumur Produksi Migas - Rachmad Maulana (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
The effect of Comparation ,Justification and Governance System on Realization of Oil and Gas Well Production as PKWT Worker (Fixed-Term Employment Contract) Certification is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Training Comparation has an effect on Oil and Gas Production Well Fixed-Term Employment Contract Certification; 2) Training Justification has an effect on Oil and Gas Production Well Fixed-Term Employment Contract Certification; and 3) Training Governance System has an effect on Oil and Gas Production Well Fixed-Term Employment Contract Certification.